Non-Performing Loans in the Albanian Banking Sector During the Global Financial Crisis: A Client Group Analysis (European Journal of Marketing and Economics, 2024)
The increase in Non-Performing Loans (NPLs) within the Albanian banking sector posed a significant challenge during the recent global economic crisis. This study investigates the specific drivers behind this issue and explores potential resolutions through an analysis of bank loans categorized by borrower groups. Given that the overall rise in business loans was largely attributed to loans extended to large enterprises, this segment forms the primary focus of the research. Based on a survey of bankers, key factors contributing to NPL growth include: financing unrealistic projects, borrowers' lack of robust corporate structures, lending decisions influenced by external factors or corruption, adverse impacts of certain government policies, intermittent unfair competition in specific sectors, declining commodity prices, and flawed external audits. A substantial majority (86%) of respondents identified more thorough client analysis, elimination of external influences and corruption in lending, government measures against unfair competition, improved corporate governance in borrowing entities, and more reliable external audits as effective remedies. However, 71% of bankers viewed the situation as typical given Albania's prevailing conditions. The study recommends that comprehensive and objective client assessments by banks, enhanced institutionalization and reliable external auditing for businesses, precise and timely government interventions against unfair competition, and the introduction of innovative financing methods will significantly mitigate the NPL problem.
Keywords: Non-Performing Loans (NPLs), Albanian Banking Sector, Financial Crisis, Business Loans, Corporate Governance, Credit Risk Management